Health Education Using Mobilephone Application To Prevent Breastfeeding Problems - Kiki Rizqi Ependi; Mekar Dwi Anggraeni; Aprilia Kartikasari ((JKG) Jurnal Keperawatan Global, 2022)
Background: Low exclusive breastfeeding rate in Indonesia is influenced by several factors. Exclusive breastfeeding rate in Indonesia is 65.16%. Breastfeeding problems affected exclusive breastfeeding duration among Indonesian breastfeeding women. Health education is needed to prevent and manage breastfeeding problems. This study aimed to analyze the effect of providing education using a mobile phone to improve mother’s knowledge about breastfeeding problems prevention. Methods: This study used a true experiment with control group pretest and posttest design. The sampling techniques used in this study was simple random sampling, consisted of 54 respondents which divided into intervention group and control group. This study was conducted in Banyumas District, Central Java province, Indonesia. The population in this study was breastfeeding mothers. The demographic characteristic questionnaire and the Breastfeeding Experience Scale (BES) were used to collect the data. All data were normally distributed and analyzed using paired t-test and independent t-test. Results: There was a significant difference between pretest and posttest scores in the intervention group (t=0.03, p<0.05) and no significant difference between in the control group (t=0.161, p>0.05). Mean of post-test scores in intervention and control group were 28.18 and 30.19, respectively. There was a difference of post-test scores between the intervention and control groups (t=0.000, p<0.05). Conclusion: The results of this study revealed that a mobilephone application has been proven effective in reducing the breastfeeding problems. We recommend develop the application to address more complex breastfeeding problems.